FAMILY SUPPORT AND IMPLEMENTATION TECHNOLOGY FOR MENTAL RETARDATION STUDENT - Susanto, Susanto (JPI (Jurnal Pendidikan Inklusi), 2018)
Every family wants all members of the family can grow and develop normally, especially children, but sometimes can not be obtained by families who have a child born with retardation mental. They feel that children with disabilities / mental retardation is a family disgrace, it is because of ignorance of families with children with mental retardation and problems the lack of information obtained. Some 15 % of the Inhabiting number of the world, or approximately the as many as one billion people, is people with disability.  Based on random survey conducted by the ministry of social affairs  of Indonesia in 1978 the population of disabled people is 3,11 % of the population in Indonesia. While the who data in 2004  estimated that the population of disabled people 10 percent of the total population of Indonesia. Data collection about the total number of voters and the population data collection about the total number of voters  of disabled people in 2004 general  election which conveyed by the central bureau of Statistics Government, based on survey 309.146 as many as a blind person around, 192. 207 deaf, 178.870 mentally retardation 94.423 defect  and other.  The data are still need the data collection system that carefull, it impeded because of factors; ignorance family and community to the issue of disability, culture of family, the stigma of the community, isolation from family, over protected, discrimination, low priority support This study aimed to get an overview of family support in the care of mentally retarded children at SLB (Special Need Education) Padangsidimpuan, Indonesia. This study used a descriptive design, samples were taken with total sampling method ( group samples are 100 family with mentally retardation and 49 children with mental retardation) and instruments used in the form of a questionnaire. Data processed by the system computerization in the frequency distribution table and percentages. Data collection was conducted on 12 July until 30 July 2011. Test reliability This research at 0.7245 by using kr 21. From research obtained good results family support as many (74%), which consists of support information (72%), support of assessment (81%), instrumental support (67%), and emotional support (74%). Family support is very important in caring for retarded children, and to increase the sense of self confidence retarded child mental. The results of this study are expected to assist nurses in providing information on family support in caring for children mental retardation.